Contraception and conception in Mid-life: a review of the current literature - Kristin Van Heertum; James Liu (BMC, 2017)
Abstract In the United States, there are an increasing number of couples who are intentionally delaying child-bearing. As the average age of mothers continues to rise, more and more women are being faced with the difficulties of attempting conception at the various stages leading up to the menopausal transition. Not only do the chances of conception drastically decrease after the age of 40 years, but the probability of fetal loss (both early and late in pregnancy) significantly increases during this period as well. The aims of this review include providing an overview of the natural progression of the menopausal transition, examining the importance of appropriate contraception, and identifying the difficulties that women face when attempting conception during this physiologically dynamic stage of life. Finally, we will discuss the non-contraceptive benefits of contraception in preparation for pregnancy during the mid-life.